The Effect of Job Stress and Job Satisfaction on Turnover Intention of Outsourcing Employees - Nindi Ayu Pravitasari (International Journal of Public Health, 2024)
The purpose of this study is to analyze: the effect of job stress and job satisfaction on turnover intentions on employees who work. This research is descriptive. This research study aims to see the extent to which the influence of the dependent variable influences the independent variable. The population in this study is all employees who work. Data were collected through a questionnaire distributed to the sample / study respondents. Secondary data were obtained from documentation, literature studies, and previous studies relating to the study material. The collected data is then analyzed statistically by descriptive analysis and multiple regression.